NVIDIA at the Center of the Generative AI Ecosystem--For Now: Assessing the ascent of NVIDIA. - Cusumano, Michael (Communications of the ACM, 2024)
The article profiles NVIDIA Corp., a manufacturer of graphical processing units (GPUs), in the context of the growth of generative AI, in which the article says GPUs play a large role.